Bifurcation and Stability of Reaction Diffusion Equations - Abdalftah Elbasir Gumah Elbori; Ali Albasher Gumma Albarki (Surman Journal of Science and Technology, 2020)
The abstract theory applies to examples of algebraic equations and nonlinear boundary value problems are discussed, including systems of reaction diffusion equations. The link s between bifurcation and stability showing are also investigated, the study discusses how increasing a diffusion coefficient in a reaction-diffusion system can lead to bifurcation and also to a stable solution becoming unstable.